Wojciech Bandrowski - zapomniany burmistrz miasta Tarnowa z lat 1867-1870 : przyczynek do biografii - Fijałkowska, Marzena (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
The beginnings of autonomy were an important period in the development of Galician towns, which coped as best as they could with the consequences of the administrative reform gradually introduced by the Austrian authorities. A key role in the process was played by mayors heading local communities, because they bore the biggest responsibility for the existence of the “little homelands”. Often, given the universal respect they enjoyed, they remained in office for several terms, wining a permanent place in the history of the town and memory of its residents. However, there were figures, like the first mayor of Tarnów, who remained forgotten for many years, which makes it all the more important to make an effort to rediscover them
Keywords: Bandrowski, Wojciech (ok. 1808-1870); burmistrz; samorząd miejski; Galicja; Tarnów